2009
DOI: 10.1242/dev.037242
|View full text |Cite
|
Sign up to set email alerts
|

dbxmediates neuronal specification and differentiation through cross-repressive, lineage-specific interactions witheveandhb9

Abstract: *Individual neurons adopt and maintain defined morphological and physiological phenotypes as a result of the expression of specific combinations of transcription factors. In particular, homeodomain-containing transcription factors play key roles in determining neuronal subtype identity in flies and vertebrates. dbx belongs to the highly divergent H2.0 family of homeobox genes. In vertebrates, Dbx1 and Dbx2 promote the development of a subset of interneurons, some of which help mediate left-right coordination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 48 publications
6
46
0
Order By: Relevance
“…For example, Truman et al found that postembryonic lineages 3 and 4 derive from embryonic NBs 7-1 and 3-1, respectively (Truman et al, 2004 The shared gene expression profiles of lineally related postembryonic and embryonic neurons suggest our gene expression map will help match postembryonic lineages to their cognate embryonic lineages. For example, in embryos NB 2-2 generates six B-type neurons that express Hb9, Nkx6 and Lim3 (Lacin et al, 2009). In larvae, lineage 10, a monotypic B-type lineage, is the only postembryonic lineage that expresses this combination of transcription factors, and similar to the embryonic neurons produced by NB 2-2, lineage 10 neurons extend axons across the midline as part of the anterior commissure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Truman et al found that postembryonic lineages 3 and 4 derive from embryonic NBs 7-1 and 3-1, respectively (Truman et al, 2004 The shared gene expression profiles of lineally related postembryonic and embryonic neurons suggest our gene expression map will help match postembryonic lineages to their cognate embryonic lineages. For example, in embryos NB 2-2 generates six B-type neurons that express Hb9, Nkx6 and Lim3 (Lacin et al, 2009). In larvae, lineage 10, a monotypic B-type lineage, is the only postembryonic lineage that expresses this combination of transcription factors, and similar to the embryonic neurons produced by NB 2-2, lineage 10 neurons extend axons across the midline as part of the anterior commissure.…”
Section: Discussionmentioning
confidence: 99%
“…4E). Truman et al (Truman et al, 2004) identified lineage 3 as the postembryonic progeny of embryonic NB 7-1, which produces Dbx + B-type embryonic neurons (Lacin et al, 2009). Thus, this NB produces Dbx + B-type neurons during embryonic and postembryonic neurogenesis.…”
Section: Research Articlementioning
confidence: 99%
“…The following primary antibodies were used: mouse anti-Abdominal B (1:20) (Celniker et al, 1989), rat anti-Elav (1:2000), mouse anti-Invected (1:2) (Patel et al, 1989), mouse anti-Sex lethal (1:10) (Bopp et al, 1991) and mouse anti-Wrapper (1:20) (Noordermeer et al, 1998) (all from Developmental Studies Hybridoma Bank); chicken anti-Beta-Gal (1:1000) (Abcam); rabbit anti-Castor (1:500) (Kambadur et al, 1998) (provided by Ward Odenwald); guinea pig anti-Dbx (1:1500) (Lacin et al, 2009) (provided by James Skeath); rabbit anti-Deadpan (1:100) (Bier et al, 1992) (provided by Harald Vaessin); rat anti-Doublesex (1:100) (Sanders and Arbeitman, 2008) (provided by Michelle Arbeitman); rabbit anti-Eagle (1:500) (Dittrich et al, 1997); rat anti-Empty spiracles (1:1000) (Walldorf and Gehring, 1992) and rabbit anti-Eyeless (1:1000) (Kammermeier et al, 2001) (provided by Uwe Walldorf); rabbit anti-Engrailed (1:100) (Santa Cruz Biotechnology); rabbit anti-Even skipped (1:1000) (Frasch et al, 1987) (provided by Manfred Frasch); mouse anti-GFP (1:250) (Roche); rabbit anti-GFP (1:500) (Torrey Pines Biolabs); rat anti-Gooseberry distal (1:2) and rat anti-Gooseberry proximal (1:2) (Zhang et al, 1994) (provided by Robert Holmgren); guinea pig anti-Hunchback (1:1000) (Mettler et al, 2006) (provided by Joachim Urban); mouse anti-Ladybird early (1:2) (Jagla et al, 1997) (provided by Krzysztof Jagla); rabbit anti-mCherry (1:500) (Bio Vision); rabbit anti-Miranda (1:100) (Betschinger et al, 2006) (provided by Juergen Knoblich); rabbit anti-Msh (1:500) (provided by Matthew Scott, Stanford University, USA); rabbit anti-Nazgul (1:400) (von Hilchen et al, 2010) and guinea pig anti-Reversed polarity (1:10,000) (provided by Benjamin Altenhein); guinea pig anti-Orthodenticle (1:500) (Xie et al, 2007) (provided by Tiffany Cook); rabbit anti-RFP (1:500) (MBL); guinea pig anti-Runt (1:500) (Kosman et al, 1998) For in situ hybridisation, we used a digoxygenin-labelled ind RNA-probe (provided by Matthew Scott). It was synthesised as described previously (Urbach and Technau, 2003b).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In the neuroblast 7-1 lineage (NB7-1), the first five neuroblast divisions produce 'U' motoneurons that express the Even-skipped (Eve) transcription factor: U1 is specified by high levels of Hb, U2 is specified by low levels of Hb, U3 is specified by Kr, U4 is specified by Pdm and U5 is specified by Cas (Isshiki et al, 2001;Pearson and Doe, 2003;Grosskortenhaus et al, 2006). GMCs that produce U motoneurons also produce Evenegative siblings, some of which transiently or permanently express the transcription factor Dbx and develop into interneurons (Lacin et al, 2009). After producing U motoneurons, NB7-1 produces only interneurons and divides five or six more times in abdominal segments of the ventral nerve cord (producing up to 22 neurons) (Bossing et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…After producing U motoneurons, NB7-1 produces only interneurons and divides five or six more times in abdominal segments of the ventral nerve cord (producing up to 22 neurons) (Bossing et al, 1996). Transcription factors that specify late-born interneuron fates and molecular markers that are specific for NB7-1 interneurons are not known, although as many as four Dbx + interneurons are produced after the motoneuron portion of the NB7-1 lineage ends (Lacin et al, 2009). …”
Section: Introductionmentioning
confidence: 99%